Phase Current Differential Protection for Transformers in Wye-delta Mode - Yuxue Wang; Xianggen Yin; Zhe Zhang; Zhenxing Li (Indonesian Journal of Electrical Engineering and Computer Science, 2012)
For the current transformers (CTs) on the delta side measure the line current instead of the phase current, line current differential protection is adopted in transformers connected in wye-delta mode currently. However, the symmetry feature of inrush current in line current differential protection may invalidate the inrush current restrained criterion. A calculating method of current through delta windings according the measured current from CT is proposed in this paper. Using this calculated current, phase current differential protection can be realized. Based on the method an adaptive second harmonic restrained scheme for magnetizing inrush current is presented. The scheme not only adaptively adjusts the secondary harmonic ratio of restrained current but also guarantees the fast action when transformers with internal faults are no-load energized. Consequently the performance of transformer differential protection is greatly improved. Simulation results in Matlab/Simulink validate the proposed method. DOI: http://dx.doi.org/10.11591/telkomnika.v10i6.1413